2015
DOI: 10.1016/j.energy.2015.10.080
|View full text |Cite
|
Sign up to set email alerts
|

Valuing crop diversity in biodiesel production plans

Abstract: The problem of defining efficient and environmentally compatible short-term agricultural plans for\ud biodiesel exploitation is dealt with in this paper with a multi-objective modelling framework. To optimally\ud use local resources, the first phase of the plan consists in the analysis of land and climate features\ud in order to evaluate which energy crop can be successfully grown. This phase is performed at local scale\ud using GIS (geographic information system) data and software. The second phase consists i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Many of the studies that had multiple objectives used optimisation or, more specifically, multi-objective optimisation as the principal study method (18 papers). In this classification, the objectives, other than economic ones, that were included in the studies were found to be as follows: ecological and biodiversity impacts [50,80], system link failure [58], terminal utilisation rate [72] and temporal variation of feedstock availability [94].…”
Section: Classification Analysismentioning
confidence: 99%
“…Many of the studies that had multiple objectives used optimisation or, more specifically, multi-objective optimisation as the principal study method (18 papers). In this classification, the objectives, other than economic ones, that were included in the studies were found to be as follows: ecological and biodiversity impacts [50,80], system link failure [58], terminal utilisation rate [72] and temporal variation of feedstock availability [94].…”
Section: Classification Analysismentioning
confidence: 99%